Flowering and fruiting of Ananas comosus L. Merr. in two cultivation systems under subtropical conditions - Levin, Sebastián (2019)
Pineapple production in the subtropics is limited by low temperatures. Frost affects the growth and development of the plants, being the main factor that compromises production. One way to mitigate this problem is the use of plastic covers (greenhouses), which could, however, negatively affect the productivity. We studied the flowering and fruiting of pineapple (Ananas comosus L. Merr.) in two cropping systems (greenhouse and field) in a subtropical region in the northeast of Argentina. Two experimental batches, with plastic covers and uncovered, divided into eight plots, were set up and phenological crop monitoring was performed. The experimental design was completely random. At the time of harvest, physical and chemical variables, such as length of fruit length with crown, fruit length without crown, equatorial diameter, density, firmness, °Brix and acidity values, were analysed to represent fruit quality. The results showed significant differences between the cultivation systems studied. Cultivation type had a marked effect on fruit quality; fruits produced in the greenhouse had a higher weight and size than those produced in the field; however, the chemical variables related to flavour did not differ significantly between the two cultivation types.